(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The results of the research pertain to the enhancement of the efficiency in utilizing the effluent waters from fish farms operating within the administrative boundaries of the Sis, Ranchpar and Hovtashat settlements in the enlarged Masis community. The study addresses the optimal utilization of agricultural lands and the development of a sustainable economic development model, aligned with the principles and requirements of Permaculture design. To achieve this objective, a comprehensive analysis was conducted on the groundwater effluents discharged from the aquaculture enterprises in the aforementioned settlements. The chemical composition and various quantitative parameters of these waters were examined. Additionally, the extent of waterlogged areas, their distribution zones, and the potential adverse effects on the fertility of agricultural soils and the surrounding environment were evaluated. In order to mitigate these negative impacts, a Permaculture-based remediation model was developed, and the feasibility of implementing this model was substantiated as a means of reducing the ecological negative consequences of aquaculture activities, while laying a foundation for the sustainable development of the economy.